Elemental Analysis of Total Suspended Particulates and PM10 in the Ambient Air of Lafarge Cement Syria and Ceramic (Fayhaa) Industry - Aziz Ramadan, Abdul; Hasan Ismail, Mahmoud; Albakour, Mohammad (Asian Journal of Chemistry, 2013)
Determination of total suspended particulates and PM10 of aerodynamics particle sizes larger than 0.3 μm and heavy metals (Pb, Cd, Cu, Cr, Ni, Fe, Mn and Zn) by atomic absorption spectroscopy in the ambient air of Lafarge Cement Syria and Ceramic (Fayhaa) Industry were studied. The mean total suspended particulates and PM10 levels in ambient air Lafarge Cement Syria were at 98 to 156 and 49 to 99 μg m-3, respectively and in ambient air Ceramic (Fayhaa) Industry were at 318 to 368 and 209 to 215 μg m-3, respectively. The above mentioned heavy metal concentrations were at 1.2 to 1.4 and 0.52 to 0.65; 0.00048 to 0.00062 and 0.00036 to 0.00047; 0.60 to 0.76 and 0.43 to 0.47; 0.092 to 0.12 and 0.081 to 0.085; 0.00017 to 0.00029 and 0.00015 to 0.00027; 2.8 to 11.1 and 2.2 to 2.9; 0.13 to 0.19 and 0.067 to 0.072; 0.094 to 0.148 and 0.065 to 0.082 μg m-3 in ambient air of Lafarge Cement Syria using total suspended particulates and PM10, respectively and in ambient air of Ceramic (Fayhaa) Industry were at 0.92 to 1.07 and 0.59 to 0.66; 0.00056 to 0.00080 and 0.00048 to 0.00076; 0.52 to 0.69 and 0.10 to 0.14; 0.047 to 0.051 and 0.031 to 0.046; 0.00038 to 0.00045 and 0.00021 to 0.00028; 2.38 to 6.42 and 1.09 to 3.27; 0.053 to 0.086 and 0.048 to 0.078; 0.153 to 0.159 and 0.114 to 0.155 μg m-3 using total suspended particulates and PM10, respectively. The results showed that the values of Pb, Mn and Fe in Lafarge Cement Syria atmosphere and total suspended particulates, PM10, Pb and Fe in ceramic (Fayhaa) industry atmosphere were more than the recommended maximum by World Health Organization, while the value levels of all metals were lower than the guideline values specified by World Health Organization.